2019
DOI: 10.1136/bjophthalmol-2019-314251
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional outcomes following switching from aflibercept to ranibizumab in neovascular age-related macular degeneration in Europe: SAFARI study

Abstract: Background/AimsProspective data on switching anti-vascular endothelial growth factors in patients with neovascular age-related macular degeneration (nAMD) who have previously shown no/partial response are limited. This prospective study assessed the effect of switching from aflibercept to ranibizumab on anatomical and functional outcomes in patients with persistent/recurrent disease activity.MethodsSAFARI (NCT02161575) was a 6-month, prospective, single-arm study conducted in the UK and Germany. Patients, meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…We found that switching from aflibercept to ranibizumab led to beneficial short-term results regarding retinal structure. Previous reports about switchback from aflibercept to ranibizumab have found similar results [18][19][20]. Compared with the monthly change before the switch, PED, IRF, and SRF showed significantly different, favorable changes postswitch.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We found that switching from aflibercept to ranibizumab led to beneficial short-term results regarding retinal structure. Previous reports about switchback from aflibercept to ranibizumab have found similar results [18][19][20]. Compared with the monthly change before the switch, PED, IRF, and SRF showed significantly different, favorable changes postswitch.…”
Section: Discussionsupporting
confidence: 61%
“…Whether the effectiveness of this drug switch is attributable to a circumvention of drug tolerance or the different pharmacologic behaviors of the drugs has been speculated. However, there is little evidence about the effect of switching from aflibercept to ranibizumab [18][19][20]. Such evidence could help to elucidate the role of drug tolerance versus pharmacological differences.…”
Section: Introductionmentioning
confidence: 99%
“…Given the longstanding ocular history of exudative AMD in our cohort, underlying structural, in part irreversible damage may contribute to a limited potential of visual recovery. [29][30][31][32] The phenomenon of disconnect between morphology and function has been observed in other switch studies of patients with nAMD. [29][30][31][32] Since the approval of brolucizumab, safety signals of development of IOI following brolucizumab treatment, ranging from anterior chamber cells to retinal vasculitis with or without occlusion and with or without moderate and severe visual loss, have been reported.…”
Section: Clinical Sciencementioning
confidence: 62%
“…A total of 100 eyes were included and nonsignificant improvements in mean macular thickness (−35.38 µm) and visual acuity (+1.9 letters) were noted at six months. In total, 34% of eyes were noted to have an increase of 5 or more letters after the switch in therapy [ 73 ]. Other smaller, retrospective studies have demonstrated similar benefits when switching to IVR in a subset of eyes with eAMD unresponsive to IVA [ 74 , 75 ].…”
Section: Exudative Age-related Macular Degenerationmentioning
confidence: 99%